DYNAMIC EFFECT CAPABILITIES ON ORGANIZATION RESILIENCE WITH DIGITAL TRANSFORMATION AS A MEDIATION VARIABLE - Yuliana Sri Purbiyati; Vincentia Devina Setyawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Whatever the organization, it is important to pay attention to dynamic capabilities . Even though there have been many studies related to dynamic capabilities, they are still relevant today. This research is a follow-up study of the same theme that the author has examined. The difference is in the research sample. This study tries to present the influence of dynamic capabilities on organizational resilience by mediating digital transformation from the point of view of school principals and their representatives. Data was taken by distributing questionnaires via Googleform as primary data. Data analysis was performed with smartPLS. From the two direct effect hypotheses, it was found that the two hypotheses proved to have a positive and significant relationship, namely, dynamic capabilities on organizational resilience and digital transformation towards organizational resilience. For an indirect relationship, significant results were also found, namely the relationship between dynamic capabilities and organizational resilience with digital transformation as a mediating variable.